Latin American congress on sexually trasnmitted diseases/Pan-American conference on AIDS - Lima, Peru: opening ceremony - Piot, Peter (Brazilian Journal of Sexually Transmitted Diseases, 1997)
Thank you for your invitation to this conference. There is a time anda place when the dispassionate language of science must yield to-or, at the very least, coexist with - che passionace prose of policies. [...]